Effect of Group Cognitive Behavioural Therapy on Loneliness in a Community Sample of Older Adults: A Secondary Analysis of a Randomized Controlled Trial. Issue 4 (8th August 2021) - Smith, Ronald; Wuthrich, Viviana; Johnco, Carly; Belcher, Jessica
ABSTRACT: Objectives: Research suggests a link between loneliness, depression, and anxiety. Multiple studies have examined treatment programs for loneliness; however, none have examined the efficacy of Cognitive Behavioral Therapy (CBT) for depression and anxiety in reducing loneliness. Methods: Change in loneliness in sixty-two older adults (≥60 yrs; 65% female) who took part in a previously reported randomized controlled trial for the treatment of comorbid depression and anxiety was examined. Older adults were randomized to a 12-week group CBT or waitlist control condition. Participants who took part in CBT were followed-up three months later. Results: Linear Mixed Model analyses indicated that after controlling for baseline cognition, depression, and anxiety, participants who completed CBT experienced a significant decrease in loneliness while the control group did not. This reduction was maintained at follow-up. Conclusions: CBT programs for depression and anxiety are likely to be effective at reducing loneliness. This may be due to shared underlying cognitive and behavioral mechanisms between loneliness, depression, and anxiety such as sensitivity to perceived threat and social withdrawal. Further research is needed to understand if specific loneliness interventions are more effective. Clinical Implications: CBT may be effective at reducing loneliness among older adults with depression and anxiety.